2019
DOI: 10.3897/zookeys.879.34404
|View full text |Cite
|
Sign up to set email alerts
|

Protura from Hainan Island, China: new species, checklist and distribution

Abstract: More than 1500 proturan specimens from Hainan Island are systematically studied. An annotated list of all species of Protura from Hainan Island is provided and their geographical distribution is discussed. The genus Paracondeellum is reported from Hainan Island for the first time, and Paracondeellum paradisumsp. nov. is described. The type species Paracondeellum dukouense (Tang & Yin, 1988) is redescribed based on syntype, and the lectotype and paralectotype are designated. The characters of the genus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Tuxen (1978b) studied also the Protura of Seychelles and he observed that fauna of Madagascar-Mascarene area includes Gondwanan species whose origin he supposed could be traced back to more than 100 my before the splitting up of the Gondwana supercontinent. Bu et al (2019) recorded 11 genera and 34 species from the island of Hainan (China), most of which belonged to Eosentomidae and Acerentomidae Berberentulinae that are widely distributed and with a high species richness in China. The fauna of this island is similar to those of neighboring mainland regions (Guangdong, Guangxi, and Yunnan provinces).…”
mentioning
confidence: 99%
“…Tuxen (1978b) studied also the Protura of Seychelles and he observed that fauna of Madagascar-Mascarene area includes Gondwanan species whose origin he supposed could be traced back to more than 100 my before the splitting up of the Gondwana supercontinent. Bu et al (2019) recorded 11 genera and 34 species from the island of Hainan (China), most of which belonged to Eosentomidae and Acerentomidae Berberentulinae that are widely distributed and with a high species richness in China. The fauna of this island is similar to those of neighboring mainland regions (Guangdong, Guangxi, and Yunnan provinces).…”
mentioning
confidence: 99%